MANAJEMEN PENDIDIKAN ISLAM ANAK USIA DINI PADA RUMAH TANGGA KARIER - Susilawati Susilawati (CV. ADIBA AISHA AMIRA, 2022)
Education is an absolute necessity for human life, since humans are born until they die. In other words, education lasts a lifetime. That is, since the baby is in the mother's womb until the grave, because education is not just for a moment, but forever. Therefore, education is a shared responsibility between families, schools and communities. Informal education is family education that is natural in this right, it is parents who play a very important role in carrying out education for their children. Management is an ability or skill to guide, supervise and treat/manage things carefully to achieve predetermined goals. Management is defined as a skill to obtain a result in order to achieve goals through the activities of others. As for the forms of implementation of Islamic religious education outside of school, among others: 1) Entering their children into recitations held in mosques, prayer rooms. 2). Involving their children in the Majlis ta'lim, 3). Islamic spiritual development in government and private institutions, 4). Provide religious courses held at the elementary school level to the university level. Like TPQ in mushollah mushollah, MTQ and others.